2017
DOI: 10.1007/s00431-017-2898-8
|View full text |Cite
|
Sign up to set email alerts
|

Adult height after spontaneous pubertal growth or GnRH analog treatment in girls with early puberty: a meta-analysis

Abstract: Present meta-analysis indicates that girls with EP spontaneously reach their MPH and that GnRH analog treatment does not widely change growth outcome. Differences among the selected studies for definition of EP, inclusion criteria, treatment duration, age at discontinuation of therapy, definition of AH may affect results. What is Known: • Early puberty represents a main cause of consultation in paediatric endocrinology offices due to concerns of both practitioners and parents. • Treatment with GnRH analogs is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 31 publications
2
16
0
1
Order By: Relevance
“…For girls with ICPP, the GnRHa and rhGH combination therapy can improve FAH by a mean of 2.81 cm over GnRHa alone as reported by Liu et al [31]. Bertelloni et al indicated that GnRHa treatment does not significantly change the growth outcome in girls with EP [32]. It is believed that the use of the combined therapy for precocious puberty and early puberty is capable of resulting in a greater FAH, and indeed the findings of the present analysis are not ideal.…”
Section: Discussionmentioning
confidence: 94%
“…For girls with ICPP, the GnRHa and rhGH combination therapy can improve FAH by a mean of 2.81 cm over GnRHa alone as reported by Liu et al [31]. Bertelloni et al indicated that GnRHa treatment does not significantly change the growth outcome in girls with EP [32]. It is believed that the use of the combined therapy for precocious puberty and early puberty is capable of resulting in a greater FAH, and indeed the findings of the present analysis are not ideal.…”
Section: Discussionmentioning
confidence: 94%
“…This corresponds to a mean age of 11.9 years at menarche, which is only slightly earlier than that of a population cohort (12.3 years) 2427. Similarly, systematic review evidence suggests that children with precocious puberty who do not receive GnRH attain a similar height to those who are treated 28…”
Section: How Is It Managed?mentioning
confidence: 89%
“…Meta‐analyses may have been missed by our search strategy for this particular analysis (which was not a systematic review). A positive note is that meta‐analyses on puberty are continually being published (e.g., Bertelloni, Massart, Miccoli, & Baroncelli, ; Deng et al., ; Durand, Tauber, Patel, & Dutailly, ; Li et al., ; Ullsperger & Nikolas, ). Given the breadth and quantity of research on puberty, meta‐analyses will continue to be particularly useful for synthesizing the literature on puberty in the future.…”
Section: Discussionmentioning
confidence: 99%